2015
DOI: 10.1111/psyg.12133
|View full text |Cite
|
Sign up to set email alerts
|

Gait speed in older people: an easy test for detecting cognitive impairment, functional independence, and health state

Abstract: The results showed that GS is an important predictor of functional capacity (physical and cognitive function) in adults over 65 years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 24 publications
2
39
2
5
Order By: Relevance
“…This deterioration in the CGT is related to a decrease in IADL, CST, HS, and GS performance. Likewise, previous studies have shown that a reduction in habitual GS is related to a reduction of functional capacity in older people [35,36]. In this regard, Callisaya et al [37] showed that several gait factors are associated with age, and sex differences in some of these associations indicate that the aging process may affect gait in men and women differently.…”
Section: Discussionmentioning
confidence: 90%
“…This deterioration in the CGT is related to a decrease in IADL, CST, HS, and GS performance. Likewise, previous studies have shown that a reduction in habitual GS is related to a reduction of functional capacity in older people [35,36]. In this regard, Callisaya et al [37] showed that several gait factors are associated with age, and sex differences in some of these associations indicate that the aging process may affect gait in men and women differently.…”
Section: Discussionmentioning
confidence: 90%
“…The significant correlation that we found between some aspects of physical performance and cognitive scores in centenarians seems important [12, 15]. As individuals grow old, motor abilities are reduced as compared with younger adults.…”
Section: Discussionmentioning
confidence: 98%
“…Both types of physical exercise are important to an independent life and previous research showed an association between exercise and cognition in middle aged and elderly individuals [11]. Gait speed is an important factor in old age, and constitutes a predictive indicator of functional capacity in older adults [12]. Handgrip strength was related to cognition in very old subjects: those with the lower values in handgrip were at higher risk of subsequent functional decline and mortality [13].…”
Section: Introductionmentioning
confidence: 99%
“…According to Bridenbaugh and Kressig () impairments in both gait and cognition are prevalent in older adults and thus, older adults with gait impairment have an increased risk of developing cognitive impairments. Garcia‐Pinillos, Cozar‐Barba, Munoz‐Jimenez, Soto‐Hermoso, and Latorre‐Roman () analysed the association between physical and cognitive functions in older people, as well as the most appropriate physical test to assess cognitive impairment, functional capacity, comorbidity and perceived health in this population. The authors showed that gait speed is an important predictor of functional capacity (physical and cognitive function) in adults over 65 years old.…”
Section: Resultsmentioning
confidence: 99%